The impact and implementation of an mHealth intervention to improve infant and young child feeding in Senegal: IIMAANJE protocol for a cluster randomized control trial - Downs, Shauna M.; Gueye, Daouda; Sall, Medoune; Ndoye, Bamba; Sarr, Ndèye Ndambao; Sarr, Moussa; Mboup, Souleymane; Alam, Neeloy Ashraful; Diouf, Adama; Merchant, Emily V.; Sackey, Joachim (Frontiers in Public Health, 2023)
Behavior change communication (BCC) strategies have the potential to improve infant feeding and nutrition outcomes among infants and young children in low- and middle-income countries. More recently, there has been a shift towards the adoption of mHealth interventions – the use of mobile phones to transmit health-related information or direct care – to promote recommended BCC strategies among the caregivers of infants and young children. In Senegal, most infants and young children are not fed according to recommended practices leading to a high prevalence of undernutrition and micronutrient deficiencies. The aims of this cluster randomized control trial, using an effectiveness-implementation (type 1) hybrid design, were to: 1) determine the impact of an mHealth IYCF intervention on IYCF practices and nutrition outcomes; and 2) examine the implementation, costs, and opportunities for scaling up the mHealth messaging intervention. The trial was conducted in three regions in Senegal (Thies, Fatick, Diourbel) with 488 mothers, father and children (6-23 months) triads. The intervention included 8 scripted messages, that underwent cognitive testing prior to the intervention implementation, and 8 unscripted messages from positive deviants. One voice message and one text message were sent each week to members of our experimental group for a 16-week period. The impact of the intervention was assessed through a household survey, 24-hour dietary recall, and hemoglobin measurements before and after the intervention implementation. The primary outcomes were minimal acceptable diet (MAD) and anemia. We also included a total of 54 participants in nine focus groups held with mothers and fathers and semi-structured interviews with Badienou Gox (i.e., community health workers) (n=6) and national partners and program implementers (n=6) to examine the intervention implementation process. The study was registered prior to data collection on Clinicaltrials.gov (Identifier: NCT05374837).